Emerging technologies for promoting food security : overcoming the world food crisis - Madramootoo, Chandra Alastair, 1954- (Elsevier/Woodhead Publishing is an imprint of Elsevier, 2016)
"Emerging Technologies for Promoting Food Security: Overcoming the World Food Crisis discusses rising energy prices, increased biofuel use, water scarcity, and the rising world population, all factors that directly affect worldwide food security. The book examines the range of approaches to promoting global food security, including novel and existing agricultural and husbandry techniques for safe and sustainable food production. It is divided into three parts beginning with an overview of food security, an analysis of key drivers of food insecurity, and nutrition and food security. Part Two examines emerging technologies for plant and animal food security, with subsequent chapters discussing topics from genetic and aquaculture technologies, pest and disease control, environmental and policy issues affecting food security, and an in-depth analysis of water management and methods to reduce post-harvest losses."--Provided by publisher
Keywords: Food security.; Food supply.; Food security -- Technological innovations.; Food supply -- Technological innovations.; Food security -- Government policy.; Food supply -- Government policy.; Food industry and trade.; Agriculture -- Economic aspects.; elektronické knihy; electronic books